Pengendalian Penyakit Layu pada Pisang dengan Bakteri Antagonis Pseudomonas fluorescens dan Bacillus subtilis - Paniman Ashna MIHARDJO; Abdul MAJID (Jurnal Pengendalian Hayati, 2008)
Fusarium wilt on bananas caused by the fungus Fusarium oxysporum f.sp cubense wereimportant and were distributed most of the centre of bananas farm in Indonesia. Both Culturetechnicaly and chemically were unable to control this pathogen because they ability to formClamydospore and to infect alternative hosts. The use of antagonistic bacteria such as Pseudomonasfluorescens and Bacillus subtilis were able to control plant pathogens both in rhizosphere or inphyllosphere because their ability to produce secondary metabolites such as siderophore, antibiotics,volatile substances, Cyanide acid, extracellular enzymes and phytohormones. This research wasconducted in Laboratory of Plant Pathology and greenhouse of Pest and Plant Diseases Department.The steps of research included exploration of antagonistic bacteria using Schaad methods,identification using Schaad, Palleron, Lelliot and Stead Methods. Last steps were done by in vitro andin vivo tests.The result showed that combination of two bacterias were able to inhibit the pathogen invitro (70,2% - 88,1%), while in vivo test with three to four applications in frequency were able todecrease disease intensity up to 81, 6%.